High performance anticorrosive epoxy paints pigmented with zinc molybdenum phosphate - Romagnoli, Roberto (1998)
Zinc molybdenum phosphate belongs to the so called second generation phosphate pigments and is claimed to have equal or greater anticorrosive properties than chromates and better than zinc phosphate alone. Little Information is available in the literature about its anticorrosive performance. The aim of this research was to stucfy the anticorrosive performance of zinc molybdenum phosphate in solvent borne epoxy paints employing two anticorrosive pigment loadings. The effect of incorporating zinc oxide as complemetary pigment was also studied SAE 1010 Steel ponéis were primed and coated with three different paint systems containing the anticorrosive paint and this paint plus a sealer cmd/or a topcoat. The anticorrosive efftciency of the different paint systems was assessed by accelerated tests (salí spray, humidity and accelerated weathering). Electrochemical measurements were done employing the anticorrosive paints alone. Results showed that the highest anticorrosive effect was obtained employing 30% of zinc molybdenum phosphate. Polarization measurements showed that the anoche film formed on Steel blocked the active sites for oxygen reduction. The incorporation of zinc oxide to pigment formula was detrimental due to its high water absorption and to the fact that it reduced zinc molybdenum phosphate solubility by the common ion effect. Polarization curves of pigments mixtures could be used as a guideline to precüct the anticorrosive coating performance in accelerated and electrochemical tests. However, the final decisión on pigment selection musí be taken on the basis of accelerated triáis.